Ginseng glycoprotein and ginsenoside facilitate anti UV damage effects in diabetic rats - Hu, Shuang; Huo, Lulu; He, Jing; Jin, Ye; Deng, Yongzhi; Liu, Da (Frontiers in Pharmacology, 2022)
Diabetes mellitus combined with ultraviolet radiation damage not only brings great mental stress to patients, but also seriously impairs their quality of life. Ginsenosides and glycoproteins have antioxidant, anti-inflammatory and apoptosis-inhibiting effects. We established a UV-irradiated diabetic rat trauma skin model, in order to investigate the effects of ginseng bark saponin and glycoprotein on skin trauma repair in diabetic combined with UV-irradiated rats and their possible mechanisms of action. In our study, we extracted ginsenosides and ginseng glycoproteins from different parts of ginseng roots, and found that ginseng bark contained more saponins, while ginseng core contained more glycoproteins. Since glycoprotein-like components are relatively novel ginseng extracts from ginseng, we specifically characterized the structures of the extracted glycoprotein-like components. It was verified that the ginseng core glycoproteins were not toxic to HaCaT cells, and they were found to significantly increase the survival of HaCaT cells after UV damage at the in vitro cellular level. In vivo experiments were conducted to evaluate the therapeutic effects of ginseng bark saponin and ginseng core glycoprotein in a rat model of diabetes mellitus combined with UV irradiation injury. Histopathological changes in rat skin after ginseng glycoprotein treatment were evaluated by H&E staining and aldehyde fuchsine staining. The expression levels of malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), matrix metalloproteinases (MMPs), hydroxyproline (HYP), interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) were measured. The results showed that both ginseng bark saponin and ginseng core glycoprotein could improve skin damage and ulcers caused by diabetes combined with UV irradiation. In conclusion, our study indicates that ginsenoside and ginseng core glycoprotein alleviate a range of skin damage caused by diabetes combined with UV irradiation, including peroxidation, inflammation, and collagen fiber loss. Ginseng bark saponins and ginseng core glycoproteins can be used as natural product candidates for the development of new drugs for the treatment of diabetes combined with UV irradiation-induced skin damage.